The effect of File type on the precision of Electronic Apex Locators / In Vitro Study/ (Journal of Hama University, 2024)
This research aims to study the precision of Woodpex III Electronic Apex Locators for the type of File mixture used in determination, nickel titanium or stainless steel.The sample included 20 single root and canal teeth and divided into two main groups (n=10 teeth each).Dental crowns were cut horizontally to provide easy access to the root canal and a stable reference point. Then the actual working length (AWL) was measured by inserting a # 10 k-file until the file tip was just visible, 0.5 mm was subtracted from this length and the new length was considered as the actual working length.In each group, the measurement was carried out using the Electronic Apex Locators, in the presence of distilled water in the channel, where the measurement was performed until the reading (0.0) was reached, and the value was taken and recorded.Measurement is carried out in the first group with a stainless steel file and in the second group with a nickel titanium file and the results are compared.Results: At the confidence level of 95%, there are no statistically significant differences in the average of working length between a group stainless steel file and nickel titanium file when using Electronic Apex Locators.There is no effect of the difference of the file used (nickel titanium-stainless steel) on the measurement precision of the Woodpex III Electronic Apex Locators.